An empirical study of the relationships between CO₂ emissions, economic growth and openness - Eunho Choi; Almes Heshmati; Yongsung Cho (Institute for the Study of Labor (IZA), 2010)
This paper investigates the existence of the environmental Kuznets curve (EKC) for carbon dioxide (CO2) emissions and its causal relationships with economic growth and openness by using time series data (1971-2006) from China (an emerging market), Korea (a newly industrialized country), and Japan (a developed country). The sample countries span a whole range of development stages from industrialized to newly industrialized and emerging market economies. The environmental consequences according to openness and economic growth do not show uniform results across the countries. Depending on the national characteristics, the estimated EKC show different temporal patterns. China shows an N-shaped curve while Japan has a U-shaped curve. Such dissimilarities are also found in the relationship between CO2 emissions and openness. In the case of Korea and Japan it represents an inverted Ushaped curve, while China shows a U-shaped curve. We also analyze the dynamic relationships between the variables by adopting a vector auto regression or a vector error correction model. These models through the impulse response functions allow for analysis of the causal variable's influence on the dynamic response of emission variables and it adopts a variance decomposition to explain the magnitude of the forecast error variance determined by the shocks to each of the causal variables over time. Results show evidence of large heterogeneity among the countries and variables impacts.
Keywords: C32; F18; F43; N55; O13; Q56; 330; carbon dioxide (CO2); environmental Kuznets curve (EKC); economic growth; free trade; development